Bibliometrics-aided retrieval: where information retrieval meets scientometrics - Glanzel, Wolfgang (Scientometrics, 2015)
This paper attempts to sketch the interrelation between information retrieval and scientometrics pointing at possible synergy effects provided by some recently developed bibliometric methods in the context of subject delineation and clustering. Examples of specific search strategies based on both traditional retrieval techniques and bibliometric methods are used to illustrate this approach. Special attention is paid to hybrid techniques and the use of ‘core documents’. The latter ones are defined merely on the basis of bibliometric similarities, but have by definition properties that make ‘core documents’ also interesting and attractive for information retrieval.